Evolutionary Potential of Parthenogenesis-Bisexual Lineages within Triploid Apomictic Thelytoky in Cacopsylla ledi (Flor, 1861) (Hemiptera, Psylloidea) in Fennoscandia - Nokkala Seppo; Kuznetsova Valentina G.; Pietarinen Peppi; Nokkala Christina (MDPI, 2025)
A widely accepted hypothesis is that parthenogenesis is an evolutionary dead end since it is selectively advantageous in the short term only but results in lowered diversification rates. Triploid apomictic parthenogenesis might represent an exception, as in favorable environments, triploid females are able to produce rare males and diploid females. The aim of the present study was to analyze the modes of reproduction and their evolutionary implications in the parthenogenetic psyllid Cacopsylla ledi (Flor, 1861) from Fennoscandia. The cytogenetic assessment of ploidy levels and the analysis of the COI haplotype revealed two geographically separated bisexual lineages implying genuine bisexual populations. The southern lineage occurring south of latitude 65° N in Finland showed a COI haplotype different from that of parthenogenetic triploids in the same population but identical to the haplotype of specimens in a genuine bisexual population in the Czech Republic. This allows us to suggest that bisexuals in southern Fennoscandia represent the original bisexual C. ledi. By contrast, in the northern bisexual lineage north of latitude 65° N, rare males and diploid females carried the same haplotype as triploids in the same population, having been produced by the triploids. In the Kola Peninsula, a genuine bisexual population of presumably rare male/diploid female origin was discovered. As this population is geographically isolated from populations of the ancestral bisexual C. ledi, it can develop into a new bisexual species through peripatric speciation during evolution. Our findings demonstrate that apomictic triploid parthenogenesis is not necessarily an evolutionary dead end but is able to lead to the emergence of a new bisexual species of parthenogenetic origin.